2018
DOI: 10.1111/cns.12993
|View full text |Cite
|
Sign up to set email alerts
|

Direct activation of tachykinin receptors within baroreflex afferent pathway and neurocontrol of blood pressure regulation

Abstract: The estrogen-dependent NKRs' expression in baroreflex afferent pathway participates at least partially in sexual-dimorphic and SP-mediated BP regulation under physiological and hypertensive conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 60 publications
(116 reference statements)
0
3
0
Order By: Relevance
“…After the primary and secondary antibodies were stained, nuclei were stained with DAPI at room temperature for 20 min. 43 …”
Section: Methodsmentioning
confidence: 99%
“…After the primary and secondary antibodies were stained, nuclei were stained with DAPI at room temperature for 20 min. 43 …”
Section: Methodsmentioning
confidence: 99%
“…SD rats were randomly divided into two groups. The hypertension group was induced by N'‐Nitro‐L‐Arginine‐methyl ester (L‐NAME), 9 which was injected intraperitoneally (40 mg/kg/d) for 4 weeks. 34 , 35 , 36 The systolic blood pressure (SBP) of all rats was measured weekly.…”
Section: Methodsmentioning
confidence: 99%
“…BRx afferent loop initiates the sensing BP fluctuation by baroreceptor terminals distributed in the aorta 1 operated by mechanosensitive PIEZOs channels 2 , 3 , 4 to the cell body of the 1 st ‐order neurons 5 , 6 in the nodose ganglia (NG), and then to the cell body of the 2 nd ‐order neurons 7 , 8 in the nucleus tractus solitarius (NTS) by forming the synapses through its central projection and the efferent loop innervates to the heart and blood vessel. Extensive animal studies have demonstrated that BRx afferent function is critical to stabilize the BP under physiological and hypertensive conditions, 7 , 9 , 10 , 11 , 12 , 13 , 14 suggesting that dysfunction of BRx afferent function is crucial for the development of both primary and secondary hypertension.…”
Section: Introductionmentioning
confidence: 99%